The phase behaviour of xanthan based biopolymer mixtures - Boyd, Matthew (2006)
It was proposed that a phase separated system might be utilised to deliver a concentrated polysaccharide mucosal protective coating in gastro oesophageal reflux disease (GORD). In this context the phase behaviour of xanthan gum in combination with sodium alginate and other polymers was studied. Above a threshold concentration of alginate, aqueous mixtures of xanthan exhibited phase separation, resulting in loss of normal viscoelastic properties and the formation of a low viscosity system. The shape of the phase diagram showed behaviour typical of a segregative system, with the continuous phase composed exclusively of alginate and the disperse phase being rich in xanthan gum. Increasing alginate molecular weight reduced the threshold concentration for separation, as predicted by the Flory-Huggins theory, but changes in alginate mannuronate:guluronate ratio had no effect. Increasing ionic strength elevated the threshold concentration. Xanthan separation was elicited by other aqueous anionic polyelectrolytes, but not neutral water soluble polymers. Scleroglucan, another rigid-rod polysaccharide, was investigated as an alternative to xanthan but did not show similar separation behaviour, suggesting that the charge on the xanthan molecule is a necessary prerequisite. Reversal of phase separation by dilution across the phase boundary provided increases in viscosity. A 1% xanthan:2% alginate mixture doubled in viscosity whereas if diluted with simulated gastric fluid a seven-fold increase was seen, as a result of conversion to an alginic acid gel. This offers a mechanism for producing the desired viscosity barrier. Low viscosity polyelectrolytes, with concentrations close to the phase boundary yielded the greatest viscosity increases. In the phase separated system, the disperse phase exhibited an unusual strand-like morphology whose birefringence suggests a liquid crystalline structure. The variable size of the strands was explained in terms of kinetics of xanthan molecular aggregation in media of different viscosity.